Perceptions and Beliefs on Vaccination for COVID-19 in Delhi: A Cross-Sectional Study - Abha Sharma; Anshuman Srivastava (Indian Journal of Medical Specialities)
Introduction: It is believed that despite all the measures taken to curb the contagion, a vaccine will be the most effective tool in preventing the spread and complications of coronavirus disease-2019 (COVID-19) and achieving a state of normalcy again. Scientists from worldwide have been successful in developing the vaccine against SARS-CoV-2, but COVID-19 vaccination faces several challenges which may impact its success. Methodology: A cross-sectional study was done to determine the beliefs and perceptions of people on COVID-19 vaccination in Delhi in the month of March–April 2021 with the help of a questionnaire which was distributed online. It contained 22 questions and was finalized after the review through a pilot study and content validation. Statistical analysis was performed using Microsoft Excel 2007. Results: A total of 286 participants were analyzed, of which 55% were female. The mean age was 33.4 years. Intention of people for taking vaccination was analyzed with relation to different age groups, and positive trend was seen in people with advancing age and it was also statistically significant (P = 0.002). It was seen that people with higher education and of higher socioeconomic status were more inclined to get vaccination; however, in our study, 39.1% of the participants were concerned about the safety of the vaccine. Conclusions: Our study demonstrated that despite repeated assurance about the safety of vaccine, people still had doubts and misconceptions which were evident from our study. Hence, this study may help the administrators to understand the community concerns, tweaking current policies, and increasing the awareness campaign so that people gather more knowledge about vaccine benefits and community trust is built.